The surgical outcomes of fixing ipsilateral femoral neck and shaft fractures: single versus double implants fixation - Yahya Alborno (14158818) (2022)
Background Combined ipsilateral femoral neck and shaft fractures are rare and present a challenging management dilemma. This study aims to assess the outcome of concomitant fixation of the ipsilateral femoral neck and shaft fracture using single versus dual surgical implants. Methods A single-center retrospective analysis of patients who underwent fixation of ipsilateral femoral neck and shaft fractures was performed over a 13-year period. Different techniques were employed to fix the complex injury. Both the reduction and the union time were assessed radiographically. Results A total of 36 patients with ipsilateral femoral neck and shaft fractures were retrospectively identified and included in the study. Twenty-four patients (66.6%) were managed with a single cephalomedullary nail, while the remaining cases were treated with two devices. All cases were operated on within an average of 3.7 ± 7.1 days. Eight patients (22.2%) developed postoperative complications. The average follow-up period was 7.3 ± 6.8 months. Although there was no statistically significant difference between the two groups, the femoral neck fractures showed shorter union time in patients treated with one implant compared to patients treated with two implants (3.0 ± 2.3 months vs. 4.2 ± 2.6 months). Another observation was that higher percentages of implant removal/failure and malunion/nonunion were seen in patients who had one implant compared to the two implants group (12.5% vs. 8.3%). Conclusion Early surgical fixation of both fractures is associated with good outcome results. No difference in outcome was observed between both groups. Correction to: The surgical outcomes of fixing ipsilateral femoral neck and shaft fractures: single versus double implants fixation: https://doi.org/10.1007/s00590-022-03411-y, published online 15 October 2022. Other Information Published in: European Journal of Orthopaedic Surgery & Traumatology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00590-022-03312-0